In vitro antioxidant capacities and antidiabetic properties of phenolic extracts from selected citrus peels - Lim, S. M.; Loh, Su Peng (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
This study aims to determine the antioxidant capacities (AC) and antidiabetic properties of phenolic extracts (free and bound) from white Tambun pomelo peels, kaffir lime peels, lime peels and calamansi peels. AC, total phenolic content (TPC) and antidiabetic properties of selected citrus peels extracts were determined pectrophotometrically using 2,2-Diphenyl-1-picrylhydrazyl free radical (DPPH) scavenging, ferric-reducing antioxidant power (FRAP), Folin-Ciocalteu (FC) and α-amylase and α-glucosidase inhibition assay, respectively. This study found that the methanolic extract of kaffir lime showed the best AC with the lowest IC50 value of DPPH radical (7.51 ± 0.50 mg/ml) and highest FRAP value [369.48 ± 20.15 mM Fe (II) E/g DW]. TPC of free phenolic extracts of all citrus peels were significantly (p< 0.05) higher compared to the bound phenolic extracts with extract of calamansi showed the highest TPC. Free- and bound phenolic extract of calamansi also had the highest α-amylase inhibition activity (61.79 ± 4.13%; 45.30 ± 5.35%) respectively. The highest inhibitory effect in α-glucosidase inhibition assay of free- and bound phenolic extracts were white Tambun pomelo (41.06 ± 10.94%) and calamansi (43.99 ± 22.03%) respectively. Hence, the citrus peels could be furthered study for their potential in management and/or prevention of diabetes.